2005
DOI: 10.1177/0898010105278929
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Frequent Mantram Repetition on Stress, Quality of Life, and Spiritual Well-Being in Veterans

Abstract: Frequent, silent mantram repetition is easily taught and could be used by nurses and patients for managing stress and increasing well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…Findings indicated significant improvements in lowering levels of perceived stress, anxiety, and anger (Bormann, 2005;Bormann, Gifford, et al, 2006;Bormann, Oman, et al, 2006;Bormann et al, 2005). A small study on the feasibility of mantram repetition indicates the potential for using this intervention to help new fathers and mothers manage their childbirth fears and anxiety (Hunter et al, 2009).…”
Section: Strategies To Decrease Paternal Fears During Childbirthmentioning
confidence: 99%
“…Findings indicated significant improvements in lowering levels of perceived stress, anxiety, and anger (Bormann, 2005;Bormann, Gifford, et al, 2006;Bormann, Oman, et al, 2006;Bormann et al, 2005). A small study on the feasibility of mantram repetition indicates the potential for using this intervention to help new fathers and mothers manage their childbirth fears and anxiety (Hunter et al, 2009).…”
Section: Strategies To Decrease Paternal Fears During Childbirthmentioning
confidence: 99%
“…Veterans and employees have reported significant reductions in stress, anxiety, anger and improvements in spiritual well-being and quality of life Bormann, Oman, et al, 2006;Bormann, Smith, et al, 2005;Bormann, Smith, Shively, Dellefield, & Gifford, 2007). HIV-infected adults have reported significant reductions in anger and increased spiritual faith/assurance (Bormann, Gifford, et al, 2006).…”
Section: Background and Significancementioning
confidence: 99%
“…The mantram intervention program has been studied in veterans with chronic illness (Bormann, Smith, et al, 2005), health care employees Bormann, Oman, et al, 2006), and HIV-infected adults (Bormann, Gifford, et al, 2006). Veterans and employees have reported significant reductions in stress, anxiety, anger and improvements in spiritual well-being and quality of life Bormann, Oman, et al, 2006;Bormann, Smith, et al, 2005;Bormann, Smith, Shively, Dellefield, & Gifford, 2007).…”
Section: Background and Significancementioning
confidence: 99%
“…The current studies used mainly female samples and may not generalize to males. A study of concentrative meditation conducted at the San Diego Department of Veterans Affairs Medical Center with a predominately male group demonstrated improvement on stress, anxiety, quality of life, and spiritual wellbeing measures [92]. With the exception of breath therapy, which used touch in the intervention, none of the studies reviewed indicated adverse reactions to meditation training.…”
Section: Meditationmentioning
confidence: 99%